البناء النفسي لدى الأطفال المعنفين أسرياً - النجار، يحيى محمود (الجامعة الإسلامية بغزة - شئون البحث العلمي والدراسات العليا, 2010)
هدفت الدراسة إلى التعرف على البناء النفسي لدي الأطفال المعنفين أسريا. وقد تكونت عينة الدراسة من (١٩٧) طف لا وطفلة ممن يدرسون في المرحلة الابتدائية في محافظتي خان يونس ورفح. وتم استخدم مقياس البناء النفسي من إعداد: الباحث. أما الأطفال الذين يعانون من العنف الأسري، فقد تم اختيارهم من خلال المرشدين التربويين الذين يعملون فـي المـدارس موضع الدراسة. وتمت المعالجة الإحصائية بواسطة اختبار(ت)، واختبار تحليل التباين، اختبـار شـفيه. \ وبينت نتائج الدراسة عدم وجود فروق ذات دلالة إحصائية في البعد العقلي والاجتماعي والدرجة الكلية تبعا لمتغير الجنس وقد أوضحت الدراسة عدم وجود فروق ذات دلالة إحصائية في جميـع مجالات مقياس البناء النفسي تعزي لمتغير الترتيب الميلادي، كما وتبين وجود فروق معنوية فـي مجال البعد الجسمي لمتغير المرحلة التعليمية الدنيا. ووجود فروق ذات دلالة إحصائية عند مستوي ٠٥,٠ للبعدين العقلي والاجتماعي لمقياس موضع الدراسة، أما باقي أبعاد المقياس فلم تظهر نتائج الدراسة فروق معنوية فيها وأشارت نتائج الدراسة إلي وجود فروق ذات دلالة إحصائية في جميع مجالات مقياس البناء النفسي تبعا لمتغير التحصيل الدراسي والدرجة الكليـة لـصالح الأطفـال الحاصلين على مستوى دراسي جيد، وجيد جدا. وبينت نتائج الدراسة إلى وجود فروق معنوية في البعد النفسي لصالح أطفال المخيم، أما باقي أبعاد مقياس موضع الدراسة فلم تظهر نتائج الدراسة فروق معنوية فيها. recent study aims at knowing the psychological structure of the children who face family violence. The study sample consisted of 197 children, males and females, who are studying at elementary stage in khanyounis and Rafah. \ The psychological structure scale was used in this study by the researcher. \ Children who are suffering from family violence were chosen by educationalist who are working at the schools where the study was conducted. \ T. Test, the test of contrast analysis and chevia test were used to the statistical analysis of the syudy. \ The findings of the study revealed that there was not any statistical significant differences regarding social and mental aspects and the total grade due to sex variable. The study also revealed that there was no statistical significant differences regarding all aspects of psychological structure scale due to birth order variable. But the study revealed that there were moral differences regarding the physical aspect due to elementary educational stage variable. There were statistical significant differences at the level 0.05 for the social and mental aspects at the measurement where the study centered on. \ But according to the last aspects of the scale, the findings of the study did not reveal any other moral differences. \ On the other hand, the findings of the study explained that there were statistical significant differences regarding to all aspects of the psychological structure scale due to studying achievement variable, and the whole grade was in advantage of the children who got the following distictions: good and a very good level. \ The findings of the study also revealed moral differences regarding psychological aspect for the favor of the camp children. Finally, the findings of the study did not reveal any moral difference regarding to the other aspects of the study scale.
Keywords: الأطفال المعنفين; للعنف الأسري; البناء النفسي